The Implementation of Communicative Language Teaching Method in Learning Speaking for Junior High School - Dewi, Nur Annisa Primasita; Ahmad, Yousef Bani; Nugraha, Sidik Indra (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to investigate teacher procedures when using the CLT technique in teaching speaking, as well as to understand students' answers and opinions about the use of CLT methods in the classroom. As a research design, the author employs interviews and field notes. The authors analyze instructors' and students' learning activities regarding speaking in the classroom using CLT utilizing interviews and field notes. The benefits of employing CLT include that teachers conduct question-and-answer sessions with students, and the frequency with which students respond to learning activities such as answering questions is increasing. As a result, one of the challenges of Communicative Language Teaching is that students continue to feel anxious and nervous if they make mistakes during the learning process. Based on the results of the study, students indicated that CLT aided them in the process of learning to speak English. This can drive students to learn since they believe that using CLT is more interactive. For students to use these strategies, teachers' roles are critical. Students find it easier to follow the learning process and gain knowledge about the role of language in learning. It is proposed that students apply the strategy in the learning process when learning speaking skills.